2017
DOI: 10.1017/cjn.2017.274
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Persons with Multiple Sclerosis Across the Continuum of Care

Abstract: Except for mental health care settings, the prevalence of MS in community, institutional and hospital-based care settings exceeded that of the general population. These data describing the sociodemographic and clinical characteristics of persons with MS may be used to inform clinical practice and policy decisions for persons with MS across the continuum of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…In this population-based cohort study, the prevalence of NH entry was 4.5%, which falls in the low end of previous reports of people with MS [3][4][5][6] but is high compared to the general population in Manitoba. 11 The NH entrants in our MS cohort were young compared to typical NH residents in the general population, with a greater burden of comorbidities over time compared to peers with MS, consistent with prior Canadian reports.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In this population-based cohort study, the prevalence of NH entry was 4.5%, which falls in the low end of previous reports of people with MS [3][4][5][6] but is high compared to the general population in Manitoba. 11 The NH entrants in our MS cohort were young compared to typical NH residents in the general population, with a greater burden of comorbidities over time compared to peers with MS, consistent with prior Canadian reports.…”
Section: Discussioncontrasting
confidence: 63%
“…11 The NH entrants in our MS cohort were young compared to typical NH residents in the general population, with a greater burden of comorbidities over time compared to peers with MS, consistent with prior Canadian reports. 5 Despite the large size of the study population and the known variability of MS, we identified relatively few trajectory groups for each of the health care services examined. There were low user groups throughout the entire period for all services.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, 8 of 10 persons with MS residing in long-term care require a wheelchair and have some degree of cognitive impairment, making long-term care admission a highly specific marker of severe disability. 19 We used ≥1 OHIP fee code for services delivered in long-term care or the long-term care code in the ODB to identify long-term care admissions 20 , 21 ; this definition has a positive predictive value of 93.2% and negative predictive value of 99.9%. 22 The earliest long-term care code identified constituted the date of disability in that setting.…”
Section: Methodsmentioning
confidence: 99%
“…A summary of pain-related data extracted from each of these peer-reviewed journal articles is provided in Table 1 . Pain prevalence rates within Canadian LTC facilities ranged from 27.1 to 75.6%, but it is important to note that methodological differences in definitions of pain, instruments used to measure pain, and populations examined existed [ 40 , 51 , 60 , 64 , 69 ]. Pain has also been shown to increase from admission to the end of residents’ stay in LTC [ 47 ].…”
Section: Resultsmentioning
confidence: 99%